2013
DOI: 10.4236/ojn.2013.32032
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing female patients’ recovery after their first myocardial infarction as experienced by cardiac rehabilitation nurses

Abstract: Background: In the developed part of the world, coronary heart disease is the major cause of death and is one of the leading causes of disease burden. In Sweden, more than 30,000 people per year are affected by myocardial infarction and out of these approximately 40% are women. Nearly 70% of the women survive and after a myocardial infarction a recovery process follows. Today's health care focuses more on treatment, symptoms and risk factors than on the individuals' perceptions of the recovery process. Aim: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Positive previous experiences in attempting to make changes, as well as improved results from diagnostic tests, were empowering factors in facilitating adaptation [ 27 , 28 ]. Consistent with previous findings, this study found that a close social network affected recovery positively, but that some patients experienced over-protection as an obstacle [ 24 , 27 , 28 ]. Although, Bergman and Bertero found that some patients with acute coronary syndrome were often unwilling to return to full-time work [ 29 ], in our study returning to work was perceived as a sign of good adjustment and a new normality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Positive previous experiences in attempting to make changes, as well as improved results from diagnostic tests, were empowering factors in facilitating adaptation [ 27 , 28 ]. Consistent with previous findings, this study found that a close social network affected recovery positively, but that some patients experienced over-protection as an obstacle [ 24 , 27 , 28 ]. Although, Bergman and Bertero found that some patients with acute coronary syndrome were often unwilling to return to full-time work [ 29 ], in our study returning to work was perceived as a sign of good adjustment and a new normality.…”
Section: Discussionsupporting
confidence: 91%
“…When necessary, their coping plans were reassessed and changed [ 26 , 27 ]. Insight into the positive aspects of their ‘new lives’ was helpful and, as suggested by Petrie et al., prompted healthier lifestyle choices, greater appreciation of health and life, improved close relationships and changes in personal priorities [ 24–27 ]. While the literature shows that the adjustment can be prolonged and is unsuccessful in approximately 30% of patients, very few patients in our study had difficulty in accepting their MI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus essential that the CRN has the possibility to discuss concerns and ways of thinking with the women so that the stress does not become pathological and interferes with their ability to recover. CRNs highlight that the need for support differs in length of time for women after an MI (Wieslander et al, 2013 ). Women have a lower level of sense of coherence and health status scores at the beginning of their recovery and 12 months later compared to men (Bergman, Årestedt, Fridlund, Karlsson, & Malm, 2012 ; Dreyer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery is described from the women's own perspective as a gradual and personal ongoing process, which includes the need for changing priorities and learning to adapt to a new life situation (Norekvål et al, 2008 ; Tobin, 2000 ) and the need to receive good care (Tobin, 2000 ). Healthcare professionals have described that women's recovery process depends both on individual factors such as their ability to cope with the stresses in life and on the available support from those around them (Wieslander, Mårtensson, Fridlund, & Svedberg, 2013 ). There is thus a paucity of research into contributory factors for promoting women's recovery and a lack of understanding as to why CRP remains underutilized among women.…”
mentioning
confidence: 99%